Black Cumin Seed Extract Decrease Motility and Shortening Mortality Time of Ascaridia galli Worm In Vitro - Vanda, Henni; Abadi, Ahmad Khairi; Hambal, Muhammad; Athaillah, Farida; Sari, Wahyu Eka; Frengki, Frengki; Daniel, Daniel (Jurnal Veteriner, 2023)
Ascaridiasis caused by roundworm Ascaridia galli is one of important diseases in poultry industry in Indonesia. This disease can affect economic losses in the form of death, growth retardation, reduced egg production as well as trigger for secondary viral or bacteria infections. Control of this nematode requires a good strategy to avoid the risk of anthelmintic resistance, one of which is the use of herbal medicine such as black cumin seed (Nigella sativa). This study was aimed to determine the level of motility and mortality time of A. galli after treated with black cumin seed extract in vitro. In this study, black cumin seed was extracted using ethanol 96%, and then diluted to 15% (P1), 25% (P2), and 45% (P3) concentration. Pyrantel pamoate preparation was used as positive control (C1), and carboxymethyl cellulose (CMC) solution as negative control (C0). Observations were carried out every 15 minutes until all the treatment worms died. The results revealed that the motility and mortality time of A. galli were significantly different in some treatment groups. The mortality time of group C0, C1 , P1, P2, and P3 were 2592, 801, 1557, 1350, and 612 minutes, respectively. 45% of black cumin seed extract had the ability to decrease worm motility, and it showed the shortest mortality time compared to other treatment groups. It can be concluded that ethanolic extract of black cumin seeds had potential anthelmintics property on A. galli worms